Comparison of Terlipressin Plus Human Albumin with Norepineprine Plus Human Albumen in Hepatorenal Renal Syndrome - Ullah, Nadeem; Muzammil, Muhammad; Tahir, Muhammad; Arif, Malik Muhammad; Rasheeq, Talha; Ather, Muhammad Mumtaz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: to evaluate the efficacy of norepinephrine plus albuman versus terlipressin plus albumin in the management of patients with type 1 HRS. Study Design: Randomized prospective study. Place and duration: medical unit of Nishter Hospital Multan from 10th June 2019 to 9th June 2020. Methodology: This study included 80 patients with type 1 HRS. Patients were randomized into two groups to receive norepinephrine plus albumin or terlipressin plus albumin. Renal functions such as serum creatinine, creatinine clearance and urine output were observed in both the groups, for baseline and after 15 days. The outcomes assessed were as follows: reversal of HRS, kidney functions, survival rate at day 30. SPSS version 23 was used for data analysis. Results: Renal analysis of terlipressin and norepinephrine was noted as 17.5% and 30%, respectively. Child-pugh score and APACHE II score of terlipressin group was 10.73±2.01 and 22.94±10.05. Child-pugh score and APACHE II score of norepinephrine group was 9.03±2.25 and 25.39±9.87. Conclusion: Norepinephrine in combination with albumin is as effective as terlipressin in combination with albumin when used for the management of hepatorenal syndrome (HRS) type 1. But easy availability and cheap rate of norepinephrine makes it alternative of terlipressin.